Epidermolysis Bullosa With Congenital Absence of Skin: Congenital Corneal Cloudiness and Esophagogastric Obstruction Including Extended Genotypic Spectrum of PLEC, LAMC2, ITGB4 and COL7A1 - Pongmee, Pharuhad; Wittayakornrerk, Sanchawan; Lekwuttikarn, Ramrada; Pakdeeto, Sasikarn; Watcharakuldilok, Piangor; Prempunpong, Chatchay; Tim-Aroon, Thipwimol; Puttanapitak, Chawintee; Wattanasoontornsakul, Piyawan; Junhasavasdikul, Thitiporn; Wongkittichote, Parith; Noojarern, Saisuda; et al. (Frontiers in Genetics, 2022)
Epidermolysis bullosa (EB) is a rare and genetically heterogeneous disorder characterized by skin fragility and blister formation occurring spontaneously or after minor trauma. EB is accompanied by congenital absence of skin (EB with CAS) in some patients. Pathogenic variants of COL7A1 are responsible for EB with CAS in the vast majority of cases. Type and subtype diagnosis of EB with CAS generally requires specific immunohistological examinations that are not widely available plus targeted gene analysis. The present study aimed to determine the clinical features of five patients affected by EB with CAS and to identify the underlying genetic defects using whole exome sequencing (WES) followed by focused analysis of the target genes. Four patients had generalized skin involvement and one had localized defects. Two patients exhibited extremely severe skin manifestations and congenital cloudy cornea along with pyloric atresia, and one had partial esophagogastric obstruction and anuria due to vesicoureteric obstruction. In the WES analysis, the average coverage of the target exons was 99.05% (726 of 733 exons), with a range of 96.4% to 100% for individual genes. We identified four novel and two known pathogenic/likely pathogenic variants of five distinct genes in the examined families: PLEC:c.2536G>T (p.Glu846Ter); LAMC2:c.3385C>T (p.Arg1129Ter); KRT5:c.429G>A (p.Glu477Lys); ITGB4:c.794dupC (p.Ala266SerfsTer5); COL7A1:c.5440C>T (p.Arg1814Cys); and COL7A1:c.6103delG. All alleles were inherited from the parents, except for the KRT5 variant as a de novo finding. The findings reveal extremely rare phenotypes of found in EB with CAS, namely congenital cloudy cornea, esophagogastric obstruction, and anuria, and extend the genotypic spectrum of EB-related genes. The data confirm that WES provides very high coverage of coding exons/genes and support its use as a reasonable alternative method for diagnosis of EB. The present data from an underrepresented population in Southeast Asia could further broaden the knowledge and research on EB.